Aerobic bacteria isolated from internal lesions of camels at Tambool slaughterhouse - Hamza, Ibtihal Ibrahim; Shuaib, Yassir Adam; Suliman, Siham Elias; Abdalla, Mohamed Abdelsalam (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This cross-sectional study was conducted from January to June 2013 to estimate the prevalence of internal lesions in slaughtered camels at Tambool slaughterhouse and to identify the aerobic bacteria colonizing these lesions. Material and methods: A total of 280 carcasses of camels were thoroughly inspected during post-mortem examination and samples were collected from internal lesions and cultured onto different culture media. Isolated bacteria had undergone testing of several biochemical activities for species identification and susceptibility to certain antibiotics. Results: Internal lesions were detected in 25.0% (95% CI of ±5.07) of the carcasses and were observed in the lungs, liver and heart. Statistical association analyses showed that origin, sex, breed, and body condition were related to detection of lesions. A number of 179 isolates of aerobic bacteria belonging to 9 genera were grown and included Staphylococcus species (32.0%), Escherichia coli (26.0%), Streptococcus species (18.0%), Corynebacterium species (5.0%), and Bacillus species, Salmonella species, Pseudomonus species, and Klebsiella species; each of them 4.0%, and Shigella species (2%). Drug susceptibility testing showed that chloramphenicol was the most effective antibiotic against Staphylococcus species, Corynebacterium species, and Bacillus species, while penicillin g 10 was more effective against Streptococcus species. Ciprofloxacin 5 µg and ampicllin/sulpactum 20 µg were effective against E. coli, Salmonella species, Klebsiella species, Shigella species, and Pseudomonas species. Conclusion: It can be concluded that internal lesions are prevalent in camels slaughtered at Tambool slaughterhouse and many species of bacteria were colonizing these lesions, hence, evaluating the economic magnitude of internal lesions resulting in partial and/or total condemnation of organs is warranted. http://doi.org/10.5455/javar.2017.d185